Structure‐based design, synthesis, and biological characterization of indolylarylsulfone derivatives as novel human immunodeficiency virus type 1 inhibitors with potent antiviral activities and favorable drug‐like profiles - Wang, Zhao; Wang, Wenbo; Gao, Zhen; Gao, Huizhan; Clercq, Erik De; Pannecouque, Christophe; Chen, Chin‐Ho; Kang, Dongwei; Zhan, Peng; Liu, Xinyong (Journal of medical virology, 2024)
In the current antiretroviral landscape, continuous efforts are still needed to search for novel chemotypes of human immunodeficiency virus type 1 (HIV‐1) inhibitors with improved drug resistance profiles and favorable drug‐like properties. Herein, we report the design, synthesis, biological characterization, and druggability evaluation of a class of non‐nucleoside reverse transcriptase inhibitors. Guided by the available crystallographic information, a series of novel indolylarylsulfone derivatives were rationally discovered via the substituent decorating strategy to fully explore the chemical space of the entrance channel. Among them, compound 11h bearing the cyano‐substituted benzyl moiety proved to be the most effective inhibitor against HIV‐1 wild‐type and mutant strains (EC50 = 0.0039–0.338 μM), being far more potent than or comparable to etravirine and doravirine. Besides, 11h did not exhibit cytotoxicity at the maximum test concentration. Meanwhile, the binding target of 11h was further confirmed to be reverse transcriptase (IC50 = 0.055 μM). Preliminary structure–activity relationship were discussed to guide further optimization work. Molecular docking and dynamics simulation studies were investigated in detail to rationalize the biological evaluation results. Further drug‐likeness assessment indicated that 11h possessed excellent physicochemical properties. Moreover, no apparent hERG blockade liability and cytochrome P450 inhibition were observed for 11h. Notably, 11h was characterized by favorable in vitro metabolic stability with moderate clearance rates and long half‐lives in human plasma and liver microsomes. Overall, 11h holds great promise as an ideal Anti‐HIV‐1 lead compound due to its potent antiviral efficacy, low toxicity, and favorable drug‐like profiles.